Prognostic significance of cyclooxygenase‐2 in cervical cancer: A meta‐analysis. Issue 2 (3rd August 2012) - Huang, Miaoling; Chen, Qing; Xiao, Jianpeng; Liu, Changhao; Zhao, Xiaomiao
Abstract Published data on the prognostic value of cyclooxygenase‐2 (COX‐2) overexpression in cervical cancer are conflicting and heterogeneous. We performed a meta‐analysis to more precisely estimate its prognostic significance. The pooled hazard ratios (HRs) or odds ratios (ORs) with 95% confidence intervals (CIs) were used to estimate the effects. Twenty‐three studies with 1, 477 cervical cancer patients were selected to evaluate the association between COX‐2 and overall survival (OS), disease‐free survival (DFS), response to chemoradiation (RC) and clinicopathological parameters. High COX‐2 expression predicted poor OS (HR: 2.53, 95% CI: 1.54–4.18), DFS (HR: 2.41, 95% CI: 1.58–3.69) and RC (OR: 3.03, 95% CI: 1.97–4.64). Subgroup analyses showed that COX‐2 overexpression was related significantly with poor OS in patients treated by chemoradiation or surgery, and in patients with squamous cell carcinoma, respectively. Besides, COX‐2 overexpression was related significantly with poor DFS in chemoradiation subgroup. Furthermore, COX‐2 overexpression was associated with poor RC in patients who received "FP" regimen or "P" regimen. Additionally, there were significant associations between COX‐2 expression and all clinicopathological parameters except tumor grade. The pooled ORs (95% CI) were as follows: 1.49 (1.09–2.04) for age, 1.77 (1.22–2.56) for lymph node metastasis, 1.04 (0.74–1.47) for tumor grade, 1.71 (1.12–2.64) for tumor size, 2.38 (1.28–4.45) for FIGO stage, 3.96 (2.32–6.77) for histological type, 2.45(1.10–5.42) for parametrical involvement. This meta‐analysis indicated that COX‐2 overexpression might be an unfavorable prognostic and a chemoradiation resistance predictive factor for cervical cancer; it could potentially help to stratify patients further in clinical treatment.